Ectopic expression of an endoparasitic wasp venom protein in Drosophila melanogaster affects immune function, larval development and oviposition. - Thomas, P.; Yamada, R.; Johnson, K.N.; Asgari, S. (Insect Molecular Biology, 2010)
Endoparasitic hymenoptera inject maternal factors into the host, along with their eggs, to subvert the host immune system. The venom protein, Vn50, previously characterized from the wasp Cotesia rubecula inhibits prophenoloxidase activation in its host Pieris rapae and in another lepidopteran, Manduca sexta. We generated a stable line in the model insect, Drosophila melanogaster, which ectopically expresses Vn50. Results indicated that Vn50 expression accelerates larval development, increases oviposition and reduces melanization in the haemolymph of the transgenic flies. Since melanization is known to be an important facet of the insect immune response, we examined the impact of Vn50 expression on susceptibility to pathogens. Transgenic Vn50 flies challenged with the fungus Beauveria bassiana had increased mortality compared with control flies, but there was no significant change in survival in flies challenged with the pathogenic bacteria, Serratia marcescens. Interestingly, mortality induced by the natural pathogen Drosophila C virus was significantly delayed in Vn50 expressing flies. This indicates a wider range of potential hosts that may be affected by Vn50 and its potential for manipulation of immune system in insects.